2019
DOI: 10.11604/pamj.2019.33.151.17601
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying odontogenic cyst associated with the impacted third molar: a case report

Abstract: Calcifying odontogenic cyst (COC) is a benign, locally aggressive, slow-growing lesion. Its occurrence constitutes about 2% of all odontogenic cysts. The most frequent sign is painless, slow growing swelling. Radiographically it appears as a well-defined unilocular radiolucency. The microscopical features of lesion showed well-delineated cystic proliferation of odontogenic epithelium with ghost cells and fibrous connective tissue wall. In the present study, 42 years old man who has COC associated with the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
(13 reference statements)
0
10
1
Order By: Relevance
“…No tumor recurrence was observed and the patient was asymptomatic. We did a research (mini-Review) for COC case report in last 6 years and we found out that among all the COC that have been reported with age range of 9 to 81 years none of the cases had recurrence and from 3 cases of CCOT all had been free of the tumor and one case of sinus CCOT had been also free of recurrence even with the same treatment procedure as ours [15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…No tumor recurrence was observed and the patient was asymptomatic. We did a research (mini-Review) for COC case report in last 6 years and we found out that among all the COC that have been reported with age range of 9 to 81 years none of the cases had recurrence and from 3 cases of CCOT all had been free of the tumor and one case of sinus CCOT had been also free of recurrence even with the same treatment procedure as ours [15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term follow-up with radiograms is recommended, since recurrence after 8 years from enucleation have been reported. It also must be underlined that recurrence carries risk of malignant transformation [30] [31]. Therefore, a long follow-up is of crucial importance in the management of this pathological entity.…”
Section: Discussionmentioning
confidence: 99%
“…It may have a central (intraosseous), or less frequently, a peripheral (extraosseous) localization. It may cause lingual expansion, displacement of teeth, root resorption, and perforation in the cortical bone [ 2 ].…”
Section: Introductionmentioning
confidence: 99%